Peran Sistem Aplikasi ERP Terhadap Manajemen Inventory Di PT XBC (International Forum of Researchers and Lecturers, 2023)
This research aims to determine the role of ERP implementation in inventory management at PT XBC's Warehouse division. This research uses a qualitative descriptive method by carrying out field study projects in the form of interviews and observations as well as case studies with the problems faced by the author. Observation was carried out in conjunction with the MSIB Batch 3 internship program which was held from 22 August to 30 December 2022 organized by Ministry of Education and Culture. Based on the results of the analysis and observation, it can be seen that there is still a need for further improvisation on the company's information system, especially in managing inventory in the Warehouse division. A good warehousing system greatly affects the relevance of stock balances from financial statements. Implementation of SOP, workflow in the division can produce effective, efficient processes without compromising the essence of information systems.